1973
DOI: 10.1159/000467986
|View full text |Cite
|
Sign up to set email alerts
|

Does Lithium Prevent Depressions by Suppressing Manias?

Abstract: 41 patients with recurrent endogenous affective disorders were given continuous lithium treatment for periods varying from 3 months to 2‘/2 years; the prophylactic action of lithium was confirmed. It was observed that a depressive episode was generally prevented or attenuated by lithium only when a preceding manic episode had been prevented or attenuated by lithium. The hypothesis of ‘subclinical’ manic phases is considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

1978
1978
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 0 publications
2
13
0
Order By: Relevance
“…a cycle of mania-depression) in rats This observation provides strong experimental support for the hypothesis that antidepressant-induced mania/hypomania is the trigger phenomenon of rapid-cycling course (Collu et al, 1997b;Serra & D'Aquila, 2008;Serra, 2009Serra, , 2010 and that the prevention of both spontaneous or antidepressant-induced mania/hypomania (Koukopoulos & Reginaldi, 1973;Koukopoulos & Ghaemi, 2009) (in neurobiological terms, dopamine D2 receptor sensitization) is essential to avoid the development of a rapid-cycling bipolar disorder.…”
Section: Antidepressants Induce a "Bipolar-like Behaviour"supporting
confidence: 60%
See 1 more Smart Citation
“…a cycle of mania-depression) in rats This observation provides strong experimental support for the hypothesis that antidepressant-induced mania/hypomania is the trigger phenomenon of rapid-cycling course (Collu et al, 1997b;Serra & D'Aquila, 2008;Serra, 2009Serra, , 2010 and that the prevention of both spontaneous or antidepressant-induced mania/hypomania (Koukopoulos & Reginaldi, 1973;Koukopoulos & Ghaemi, 2009) (in neurobiological terms, dopamine D2 receptor sensitization) is essential to avoid the development of a rapid-cycling bipolar disorder.…”
Section: Antidepressants Induce a "Bipolar-like Behaviour"supporting
confidence: 60%
“…The prevention of mania, whether induced by antidepressants or spontaneous, is the essential element in the therapy and prophylaxis of bipolar disorders (Koukopoulos & Reginaldi, 1973;Koukopoulos & Ghaemi, 2009). When, in fact, treatments currently in use do not achieve this aim the course of the disorder becomes 'malign', i.e refractory to treatment, as in the rapid-cycling course.…”
Section: Antidepressants Induce a "Bipolar-like Behaviour"mentioning
confidence: 99%
“…Antidepressant induced manic episodes in humans [38,41,49,50] and dopamine receptor sensitization should be considered not a mere iatrogenic phenomenon but the intensification of a spontaneous underlying hypomanic process. In fact, the conversion from unipolar to bipolar course induced by antidepressants persists also after the discontinuation of antidepressant treatment, suggesting that these drugs anticipate a natural phenomenon.…”
Section: Antidepressants Induce a "Bipolar-like" Behaviormentioning
confidence: 99%
“…Other workers, more recently, have also been impressed by the frequency with which depression follows mania (41,53). One study demonstrated that almost 60% of all manic attacks were followed by depression; sadness and dysphoria were frequent in the remainder but of insufficient intensity to qualify for the diagnosis of clinical depression (82).…”
Section: Patterns Of Manic Depressive Illnessmentioning
confidence: 99%
“…If this can be demonstrated, it would provide an explanation for lithium's antimanic and prophylactic actions in manic-depressive illness (71). In preventing monoamine oxidase inhibition lithium also prevents its later rebound; in blocking one swing of the metabolic pendulum, lithium also blocks the other (41) (fig. 1).…”
Section: Evidence From Lithium and The Antidepressant Drugsmentioning
confidence: 99%